Enhancing Leave Management through an Online Employee Leave Application System - Munawir, Ahmad; Pratama, Gelard Untirtha; Auliana, Sigit; Rohman, Ali; Rizki, Miftahul (ARRUS Journal of Engineering and Technology, 2024)
The manual leave application process at PT. Citra Bonanza Expresspresents several challenges, including inefficiencies and potential errors in leave recording. This study aims to develop and implement a web-based leave application system to address these issues. Utilizing the waterfall methodology, the system development involved requirement analysis, system design, implementation, testing, and maintenance. The results demonstrate significant improvements in efficiency, accuracy, and transparency. The automated system streamlines the leave application and approval processes, eliminates errors, and provides real-time access to leave information. Comprehensive reporting capabilities enable data-driven decision-making for management. The successful deployment of the system underscores its potential applicability in other organizations with similar challenges.